3(39u+60)=-9(5u-128)

Simple and best practice solution for 3(39u+60)=-9(5u-128) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(39u+60)=-9(5u-128) equation:



3(39u+60)=-9(5u-128)
We move all terms to the left:
3(39u+60)-(-9(5u-128))=0
We multiply parentheses
117u-(-9(5u-128))+180=0
We calculate terms in parentheses: -(-9(5u-128)), so:
-9(5u-128)
We multiply parentheses
-45u+1152
Back to the equation:
-(-45u+1152)
We get rid of parentheses
117u+45u-1152+180=0
We add all the numbers together, and all the variables
162u-972=0
We move all terms containing u to the left, all other terms to the right
162u=972
u=972/162
u=6

See similar equations:

| 2288=44(p+25) | | 15v-12v-2v=18 | | 4b-5(b-1)=5b+1 | | 5(t+4)=6t-t+(11+9) | | (x÷2)+44=100 | | 3248237498x238472346238974x(2389471=37832)+9823230948283879238759823759823640983273 | | 10p-p=11 | | 10p−-p=11 | | 5x+60=76 | | G=7/4(p-80) | | 3(39u+60)=-9(5u-128 | | 5q-3q-q-q+q=12 | | 19r-8r-10r=7 | | -109=-8(x+8)-5 | | 4t+5t+7=7+9t | | 1a+3=a-12 | | 19r−8r−10r=7 | | 5d+15=2d-6 | | -6a-3a=0 | | 9r+4r+r-12r-r=8 | | 4(t+6)=4t+20 | | 9r+4r+r−12r−r=8 | | 3x+7-3=-8 | | 11.73=-0.1d+19.4 | | 2v+3=33 | | -4.2+g=12.7 | | 1a+3=-12 | | 3/5f-4/5=2-4 | | x/0.25=13 | | x+3/12=5/6+x-2/3 | | X+2/2=6-x+3/3 | | 7x-1x=0 |

Equations solver categories